Continuous IV infusion of anakinra - Saunders, Brittney N.; Kuijpers, Marcela V.; Sloan, Jason J.; Gertner, Elie (Frontiers in Pharmacology, 2023)
Objective: A review of the use of continuous IV infusion of anakinra; a description of the Regions Hospital protocol for continuous IV infusion of anakinra in the treatment of cytokine storm developed over the past 4 years. Methods: We reviewed published reports of continuous IV infusion of anakinra in cytokine storm and summarize this method of treatment in other diseases. As well, over the past 4 years, continuous IV infusions of anakinra were administered at our institution for approximately 400 patient days of treatment primarily for the cytokine storm associated with macrophage activation syndrome (MAS) in adults. The updated Regions Hospital protocol is presented. While this a single center protocol, it may serve as an initial guide for further refinement of protocols in MAS and other conditions. Conclusion: Continuous IV infusion of anakinra has advantages over subcutaneous infusions and may be important in controlling severe life-threatening cytokine storm as seen in macrophage activation syndrome. This has the potential to be an important therapy for other syndromes including Cytokine Release Syndrome related to CAR T-cell therapy. Close collaboration between Rheumatology, Pharmacy and Nursing allows this treatment to be delivered rapidly and efficiently.